Quality Indicators in a Mixed Adult ICU in Nepal: An Observational Study - Sharma, Rishav; Mali, Sharmila (Grande Medical Journal, 2025)
Background: Quality indicators (QIs) are vital for assessment of the performance of intensive care units (ICU) and guiding further improvement. In Nepal, systematic evaluation of these indicators remains scarce. This study aimed to evaluate structural, process, and outcome-based QIs in a Level III mixed adult ICU in Kathmandu, Nepal. Method: A retrospective observational study was conducted at Grande International Hospital’s ICU, including all admissions during 2024. Data were extracted from routinely maintained hospital records and analyzed using Microsoft Excel 2024. Result: The ICU had 11 beds and admitted 768 patients in 2024. The occupancy rate was 63.7%, with a median length of stay of 3 days. The nurse-to-patient ratio of 1:1 was maintained. Hand hygiene compliance was 58%, while 82.2% of eligible mobilization days were fulfilled. A total of 118 patients received invasive mechanical ventilation during the study period. Among mechanically ventilated patients, venous thromboembolism (VTE) prophylaxis was provided on 93.6% of days and spontaneous awakening trial (SAT) was performed on 54.4% of days. The reintubation rate within 48 hours was 23.9%. The mortality rate was 10.3%, and the standardized mortality ratio (SMR) was 0.79. Culture-proven ICU-acquired infection rate was 2.8%, with central line associated blood stream infection (CLABSI), catheter associated urinary tract infection (CAUTI), and ventilator associated pneumonia (VAP) rates of 1.98, 1.97, and 13.04 per 1,000 device-days, respectively. Conclusion: The ICU demonstrated strong structural capacity and favorable outcomes, especially in SMR. However, improvement is needed in hand hygiene compliance and sedation practices. Regular QI audits may help strengthen ICU care quality.